Antisense oligonucleotides targeting angiotensinogen: insights from animal studies - Wu, Chia-Hua (Biosci Rep, 2019)
Angiotensinogen (AGT) is the unique substrate of all angiotensin peptides. We review the recent preclinical research of AGT antisense oligonucleotides (ASOs), a rapidly evolving therapeutic approach. The scope of the research findings not only opens doors for potentially new therapeutics of hypertension and many other diseases, but also provides insights into understanding critical physiological and pathophysiological roles mediated by AGT.